Caveolin-1, GATA-3, and Ki67 expressions and their correlation with pathological findings in canine bladder urothelial carcinoma - Govoni, Verônica Mollica [UNESP]; Pigoli, Claudio; Brambilla, Eleonora; Ruiz Sueiro, Felipe Augusto; Torres Neto, Rafael; Laufer-Amorim, Renee [UNESP]; Gomes Quitzan, Juliany [UNESP]; Grieco, Valeria; Fonseca-Alves, Carlos Eduardo [UNESP] (Frontiers, 2022)
The bladder urothelial carcinoma (UC) represents ~2% of malignant neoplasms in dogs and is a therapeutic challenge in veterinary medicine. Although it is considered the most common bladder cancer in dogs, few previous studies have investigated different markers that correlate with clinical and pathological parameters. Therefore, this study aimed to evaluate Caveolin-1, GATA-3, and Ki67 immunostaining in canine UC samples to evaluate their correlations with histopathological variables. Thirty tumor samples were obtained, and Caveolin-1, GATA-3, and Ki67 expression was assessed by immunohistochemistry and associated with pathological factors by univariate and multivariate analyses. Among the histopathological findings, lymphatic invasion was identified in 53.33% of the tumors, and the mean mitotic count (MC) was 31.82 ± 26.26. Caveolin-1 showed mild-to-high cytoplasmic expression in neoplastic cells, whereas GATA-3 showed mild-to-high nuclear expression. The Ki67 expression revealed a mean of 24.14 ± 16.88% positive cells. In the univariate analysis, no association was found between each marker and the pathological findings. On the other hand, in multivariate analysis, we identified a positive correlation between GATA-3 and MC and a negative correlation between Caveolin-1 and MC. Moreover, lymphatic invasion was positively correlated with histological type and grade, and negatively correlated with MC. In addition, the histological type was positively correlated with the histological grade. Overall, our results indicate that Caveolin-1 and GATA-3 expression could be promising markers for bladder UC aggressiveness.
Keywords: biomarker; cancer; dog; immunohistochemistry; neoplasia